Doktrin Gereja (Eklesiologi) - Gaeldrieno Gaeldrieno; Anom Zatmiko (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
The doctrine of the Church, or ecclesiology, is an essential part of Christian theology that focuses on the understanding, function, and role of the Church as the body of Christ. The Church is not only understood as a physical institution but also as a community of faith that serves to glorify God, minister to others, and proclaim the Gospel. This study explains the importance of church doctrine as the foundation for forming congregational identity, spiritual growth, and as a guide in worship and ministry practices. Furthermore, this paper describes the positive impact of church doctrine on the spiritual development and social life of the congregation, as well as the challenges faced in the context of social, cultural, and technological change. The Church is expected to respond to these challenges through doctrinal education, community strengthening, and a contextual approach so that its teachings remain relevant and can be practically applied in the lives of believers.